Implementation of Sustainable Food Agricultural Land Protection Policy in Sukabumi City, West Java, Indonesia - Nita Inopianti; Khursatul Munibah; Moh. Yanuar Jarwadi Purwanto (International Journal of Business, Economics, and Social Development, 2021)
The population increase and regional development are causes of decreasing agricultural land. For supporting agricultural land protection, Sukabumi City issued a Regional Regulation Number 1 of 2016 concerning Sustainable Food Agricultural Land Protection Policy in Sukabumi City (LP2B) which determines 321 ha land as eternal agricultural land. This study examines a level LP2B policy implementation in Sukabumi City. Factors that will be considered: the level of land readiness as LP2B, the level of an implementation incentive program, the level of response and availability of farmers, and the level of infrastructure and information systems readiness. The analytical method used is a descriptive method through collecting data by interviewed farmers, government and reviewing documents related to LP2B policies. The results of the study show that for land readiness, in early 2021 Sukabumi city is ready for about 10.024% % from total planned land. For the implementation of LP2B incentive program, the majority of farmers has not experienced the incentive program. For the farmer’s response and availability, the majority of farmers does not know about LP2B policy, 80% of owner farmers are ready to provide their land into LP2B with some conditions. The availability of irrigation infrastructure in Sukabumi City is very good, where more than 75% of respondents rice fields has an irrigation system. Related to LP2B information system, Sukabumi City has issued a Mayor Regulation Number 8 of 2018 concerning LP2B Information System in Sukabumi City, but this system has not been optimal in providing basic information that is required to exist in a LP2B information system.